Neuromuscular and Cardiovascular Adaptations in Response to High-Intensity Interval Power Training. Issue 1 (January 2018) - Romero-Arenas, Salvador; Ruiz, Rubén; Vera-Ibáñez, Antonio; Colomer-Poveda, David; Guadalupe-Grau, Amelia; Márquez, Gonzalo
Abstract : Abstract: Romero-Arenas, S, Ruiz, R, Vera-Ibáñez, A, Colomer-Poveda, D, Guadalupe-Grau, A, and Márquez, G. Neuromuscular and cardiovascular adaptations in response to high-intensity interval power training. J Strength Cond Res 32(1): 130–138, 2018—The aim of this study was to determine the efficacy of a high-intensity power training (HIPT) program, and to compare the effects of HIPT to traditional power training (TPT) on the aerobic and power performance. For this purpose, 29 healthy men (23.1 ± 2.7 years) were recruited and randomly distributed into 3 different groups. One group performed TPT ( n = 10), the second group performed power training organized as a circuit (HIPT; n = 10), and the third group served as control group (CG; n = 9). Training consisted of weightlifting thrice per week for 6 weeks. The TPT subjects performed 3 to 5 sets of each exercises with interset rest of 90 seconds, and HIPT subjects executed the training in a short circuit (15 seconds of rest between exercises). To know the effects in aerobic performance, maximal aerobic speed (MAS) was measured. To identify the effects on power performance, subjects performed a Wingate test, a countermovement jump (CMJ) test, and a power-load curve in bench press. The main results showed that after both power training protocols, subjects increased significantly ( p ⩽ 0.05) the power production during the Wingate Test, the height and power reached during the CMJ test, and the peak power produced during the power-load curve. However, only the HIPT group improved significantly MAS ( p ⩽ 0.05). There were no changes in any variables in CG. Hence, our results suggest that HIPT may be as effective as TPT for improving power performance in young adults. In addition, only HIPT elicited improvements in MAS.